Synthetic Teammate Communication and Coordination With Humans. (September 2015) - Demir, Mustafa; McNeese, Nathan J.; Cooke, Nancy J.; Ball, Jerry T.; Myers, Christopher; Frieman, Mary
A synthetic teammate based on ACT-R cognitive architecture has been developed to function as an Air Vehicle Operator in the context of a three-agent Unmanned Aerial Vehicle (UAV) ground control team taking part in studies in a Synthetic Task Environment (STE). In order for the synthetic teammate to function as team player with human teammates, it needs to skillfully handle the subtleties of team communication and coordination. Data from early synthetic teammate interactions with two human teammates are presented here to illustrate team communication and coordination challenges for the synthetic teammate. In turn, the synthetic teammate limitations have highlighted the intricacies involved in effective teamwork. Communication, though a terrifically challenging problem in itself, is only a foundation for coordinated teamwork or interacting as a team player.